Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

There are some values: $$ a^{2\alpha }, \quad (a^{\alpha})^{2}, \quad (a^{2})^{\alpha }.$$ How to prove that the sets of these values ​​are not equal?

Addition 1. For example, I used one simple task equal to $\left(z^{2}\right)^{\alpha}$.

Let's have two values: $z^{\frac{m}{n}}: z^{\frac{m}{n}}, \quad \left(z^{\frac{1}{n}}\right)^{m}$, where $n, m$ are not integer in general. Without loss of generality we can assume, that |z| = 1. $$z^{\frac{m}{n}} = e^{i\frac{m}{n}(\varphi + 2\pi k)} = cos\left(\frac{m}{n}\left( \varphi + 2 \pi k\right)\right) + isin\left(\frac{m}{n}\left( \varphi + 2 \pi k\right)\right).$$ $$\left(z^{m}\right)^{\frac{1}{n}} = cos\left(\frac{m}{n}\left( \varphi + 2 \pi k \right) + 2m\pi j\right) + isin\left(\frac{m}{n}\left( \varphi + 2 \pi k \right) + \frac{1}{n}2\pi j\right).$$ There are difference sets of values.

Addition 2. Previous example was bad. So I created new example: for $\alpha = x + iy$ $$\left(a^{\alpha}\right)^{2} = \left(e^{xln(r) - y(\varphi + 2 \pi k)}[cos(x (\varphi + 2 \pi k) + yln(r)) + isin(x (\varphi + 2 \pi k) + yln(r))]\right)^{2} = $$ $$ = e^{2xln(r) - 2y(\varphi + 2 \pi k)}[cos(2x (\varphi + 2 \pi k) + 2yln(r)) + isin(2x (\varphi + 2 \pi k) + 2yln(r))],$$ $$\left(a^{2}\right)^{\alpha} = e^{2xln(r) - y(2\varphi + 2 \pi k)}[cos(x (2\varphi + 2 \pi k) + 2yln(r)) + isin(x (2\varphi + 2 \pi k) + 2yln(r))].$$

Can somebody generalize this result?

share|improve this question
    
They certainly look equal to me. Is there more information to the question? –  EuYu Sep 13 '12 at 17:49
    
Unfortunately, it isn't. But as the answer says that the values ​​are not equal. –  John Taylor Sep 13 '12 at 17:54
    
Are you sure you don't mean $a^{2\alpha}, a^{\alpha^2},$ and $a^{2^\alpha}$? –  Tarnation Sep 13 '12 at 17:57
    
Of course, I'm sure. –  John Taylor Sep 13 '12 at 17:59
    
What is the source you refer to? That is, where is that answer? –  AD. Sep 13 '12 at 18:03

1 Answer 1

up vote 1 down vote accepted

Take $a=-1$ and $\alpha=\frac12$. Then $a^{2\alpha}=(-1)^{2\cdot1/2}=(-1)^1=-1$, but $(a^2)^\alpha = ((-1)^2)^{1/2}=1^{1/2}=1$ (or $\pm1$ when using the complex multivalued definition).

The following considerations all use the complex multivalued definition.

For real exponents, we can restrict to bases of the form $r\mathrm e^{\mathrm i\phi}$.

Then we have $a^{2\alpha}=\{\mathrm e^{\mathrm i\alpha(\phi+2\pi k)}:k\in\mathbb Z\}$ and $(a^\alpha)^2=\{\mathrm e^{2\mathrm i\left(\alpha(\phi+2\pi k)+2\pi j\right)}:j,k\in\mathbb Z\}=\{\mathrm e^{2\mathrm i\alpha(\phi+2\pi k)}:k\in\mathbb Z\}$ because the term proportional to $j$ is always an integer mutiple of $2\pi$.

Therefore we see that for all real $\alpha$ we have $a^{2\alpha}=(a^\alpha)^2$. Indeed, the same argument can be used to show that for all real $\alpha$ and integer $n$, we have $a^{n\alpha}=(a^\alpha)^n$.

For pure imaginary exponents $\alpha = \mathrm i\beta$, we have with $a=r\mathrm e^{\mathrm i\phi}$: $$a^{2\alpha} = a^{2\mathrm i\beta} = \mathrm e^{2\mathrm i\beta\left(\ln r + \mathrm i(\phi+2\pi k)\right)} = \mathrm e^{-2\beta(\phi+2k\pi)+2\mathrm i\beta\ln r}$$ and $$(a^\alpha)^2 = (a^{\mathrm i\beta})^2 = (\mathrm e^{-\beta(\phi+2k\pi)+\mathrm i\beta\ln r})^2 = \mathrm e^{-2\beta(\phi+2k\pi)+2\mathrm i\beta\ln r + 2\cdot2\pi\mathrm i j} = a^{2\alpha}$$ because again, the exponents only differ by an integer multiple of $2\pi\mathrm i$. Again, this can be extended to arbitrary $n\in \mathbb Z$.

Nor for arbitrary complex exponents, first note that $a^{\alpha+\beta}=a^\alpha + a^\beta$ (this follows directly from the properties of the exponential function and the fact that complex number multiplication is commutative). Therefore especially $a^{x+\mathrm iy} = a^xa^{\mathrm iy}$.

Furthermore, for the multivalued definition of the power (unlike the principal value definition), we have $(ab)^c = a^cb^c$, as can be seen as follows: $$a^c b^c = \mathrm e^{c(\ln a + 2\pi\mathrm i j)}\mathrm e^{c(\ln b + 2\pi\mathrm i k)} = \mathrm e^{c(\ln a + \ln b + 2\pi\mathrm i (j+k))} = \mathrm e^{c(\ln (ab) + 2\pi\mathrm i (j+k))} = (ab)^c$$

Therefore with $\alpha = x+\mathrm iy$ and the previous results, we have always $$(a^\alpha)^2 = (a^xa^{\mathrm iy})^2 = (a^x)^2(a^{\mathrm iy})^2 = a^{2x}a^{2\mathrm iy} = a^{2x+2\mathrm iy} = a^{2\alpha}$$

Again, the same argumentation applies for any integer instead of $2$.

Conclusion

For the multivalued definition of the complex power, for any complex $a$ and $\alpha$ and every integer $n$ we have $${a^\alpha}^n = a^{n\alpha}$$ However we generally (but not always) have $${a^n}^\alpha \ne a^{n\alpha}$$ One obvious exception to the second inequality is where $\alpha\in\mathbb Z$.

share|improve this answer
    
Maybe there are some complex values that create a differense in the sets of values? –  John Taylor Sep 13 '12 at 18:13
    
Let's have two values: $z^{\frac{m}{n}}: z^{\frac{m}{n}}, \quad \left(z^{\frac{1}{n}}\right)^{m}$. Without loss of generality we can assume, that |z| = 1. $$z^{\frac{m}{n}} = e^{i\frac{m}{n}(\varphi + 2\pi k)} = cos\left(\frac{m}{n}\left( \varphi + 2 \pi k\right)\right) + isin\left(\frac{m}{n}\left( \varphi + 2 \pi k\right)\right).$$ $$\left(z^{\frac{1}{n}}\right)^{m} = cos\left(\frac{m}{n}\left( \varphi + 2 \pi k \right) + 2m\pi j\right) + isin\left(\frac{m}{n}\left( \varphi + 2 \pi k \right) + 2m\pi j\right).$$ There are difference sets of values. –  John Taylor Sep 13 '12 at 20:48
    
@Maxim_Ovchinnikov: $\frac{m}{n}(\phi+2\pi k)+2m\pi j = \frac{m}{n}(\phi+2\pi (k+nj)) = \frac{m}{n}(\phi+2\pi k')$. Since $k$ may be any integer, the sets are the same. However, if $\alpha$ is irrational, the sets should be indeed different. –  celtschk Sep 14 '12 at 9:05
    
Can you show that? –  John Taylor Sep 14 '12 at 13:20
    
Yes, I understood, that that example was bad. I created new example: for $\alpha = x + iy$ $$\left(a^{\alpha}\right)^{2} = \left(e^{xln(r) - y(\varphi + 2 \pi k)}[cos(x (\varphi + 2 \pi k) + yln(r)) + isin(x (\varphi + 2 \pi k) + yln(r))]\right)^{2} = $$ $$ = e^{2xln(r) - 2y(\varphi + 2 \pi k)}[cos(2x (\varphi + 2 \pi k) + 2yln(r)) + isin(2x (\varphi + 2 \pi k) + 2yln(r))],$$ $$\left(a^{2}\right)^{\alpha} = e^{2xln(r) - y(2\varphi + 2 \pi k)}[cos(x (2\varphi + 2 \pi k) + 2yln(r)) + isin(x (2\varphi + 2 \pi k) + 2yln(r))].$$ –  John Taylor Sep 14 '12 at 13:27

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.